2022
DOI: 10.3390/polym14142783
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical, Mechanical, Biopharmaceutical Properties of Emulgels and Bigel Containing Ciclopirox Olamine

Abstract: Emulsions are thermodynamically unstable systems and it is difficult to produce biphasic formulations with large amounts of oil. The aim of our study was to prepare biphasic formulations containing 1% ciclopirox olamine and to determine the influence of the method of oil incorporation (without and with emulsifier and gelifier) on the physical (pH, particle size, rheological properties), mechanical, and biopharmaceutical properties of the formulations. It was found that the use of a poloxamer 407 gel as the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The higher consistency values tend to result in the sample having a thicker and harder form. From a biopharmaceutical perspective, products with a low consistency can be more thoroughly applied on the skin and more easily absorbed [ 74 ]. The lowest consistency was determined in the 5/95 sample (315.54 g·s), and the bigels with ratios 10/90, 15/85, 20/80, 25/75, 30/70 had similar values (324.03–331.69 g·s).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher consistency values tend to result in the sample having a thicker and harder form. From a biopharmaceutical perspective, products with a low consistency can be more thoroughly applied on the skin and more easily absorbed [ 74 ]. The lowest consistency was determined in the 5/95 sample (315.54 g·s), and the bigels with ratios 10/90, 15/85, 20/80, 25/75, 30/70 had similar values (324.03–331.69 g·s).…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have described index of viscosity as the extrusion energy or work of adhesion when it becomes higher [ 74 , 77 , 78 ]. In this study, it was observed that the higher the cohesiveness, the stronger the inner intermolecular bonds in the sample of the bigel and the lower the adhesion to the tool of the device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, 2 g of sample (ANG 12) was stored at −20 °C for 24 h into a 5 ml Eppendorf tube. After 24 h, the Eppendorf tube was kept at 22 °C and thawed for 5 h. The freeze-thawing process was repeated in triplicate and analysed for any change in appearance at the end of every cycle ( Mazurkeviciute et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…20 Various bigel systems have recently been reported in the literature aiming to explore the general characteristics of bigels or to provide comprehensive knowledge of bigels as fat mimetics. Bigels were formulated using GMS, [20][21][22][23][24][25][26] waxes, 15,[27][28][29] ethyl cellulose 25,30 and a lecithin-stearic acid mix 31 as the oleogelators, while gelatin, 20,25,28,29 gums, 21,32 κ-carrageenan, 23,24 alginate 15,33 and others were used as the hydrogelators. The bigels' mixing procedure is commonly achieved by mixing two hot phases at temperatures higher than 70 °C (ref.…”
Section: Introductionmentioning
confidence: 99%